1985
DOI: 10.1111/j.1432-1033.1985.tb09191.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a 26-kDa-protein mRNA in human cells treated with an interleukin-1-related, leukocyte-derived factor

Abstract: A human‐leukocyte‐derived antiviral protein (22‐kDa factor), known to be an inducer of interferon‐β (IFN‐β) in fibroblastoid cells, and to be closely related to interleukin‐1 (IL‐1), was shown to likewise act as inducer of the mRNA of a 26‐kDa secreted protein. This protein was first described as the gene product of an mRNA that is co‐induced with the mRNA of IFN‐β by superinduction of fibroblasts (treatment with dsRNA and cycloheximide). Subsequently it was shown to be induced by treatment with cycloheximide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
1
3

Year Published

1987
1987
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(59 citation statements)
references
References 24 publications
2
52
1
3
Order By: Relevance
“…Recently, it has been demonstrated that fibroblasts can produce cytokines when stimulated with immunomodulators such as lipopolysaccharide or phorbol myristate acetate [33] or with cytokines themselves [34]. Therefore, it cannot be excluded that the effects observed in our experiments could be partly due to cytokines secreted by the fibroblasts as a result of TNF stimulation.…”
Section: Sds-page Analysis Of Radiolabelled Collagens and Fibronectincontrasting
confidence: 39%
“…Recently, it has been demonstrated that fibroblasts can produce cytokines when stimulated with immunomodulators such as lipopolysaccharide or phorbol myristate acetate [33] or with cytokines themselves [34]. Therefore, it cannot be excluded that the effects observed in our experiments could be partly due to cytokines secreted by the fibroblasts as a result of TNF stimulation.…”
Section: Sds-page Analysis Of Radiolabelled Collagens and Fibronectincontrasting
confidence: 39%
“…IL-6 is induced in various cell types by a plethora of activators. Among the strongest and first identified are the proinflammatory cytokines tumor necrosis factor (TNF) (21) and IL-1 (22). Expression of IL-6 is controlled by transcriptional and post-transcriptional mechanisms.…”
mentioning
confidence: 99%
“…Further, the gene coding for the 26-kDa protein is also induced by a highly purified interleukin 1ip (IL-1p3)-related protein obtained from con A-stimulated human leukocytes (5), later demonstrated to be identical to IL-1f3 (6). Although it has been claimed that the 26-kDa protein has a weak IFN-like activity-neutralized by anti-IFN-p8 sera-the biological function of this molecule remained mysterious until the recent report of an identical cDNA sequence coding for an interleukin, active on Blymphocytes (7)(8)(9), and having a potent growth factor activity on the same cells (10).…”
mentioning
confidence: 99%